Autonome Praxis und intelligible Welt : die transzendental-praktische Freiheit in Kants Lehre vom hochsten Gut - Faizzada, Walid. (Critical Studies in German Idealism, 2017)
In Autonome Praxis und intelligible Welt: Die transzendental-praktische Freiheit in Kants Lehre vom höchsten Gut Walid Faizzada reconstructs Kant's theory of freedom in light of modern debates about determinism and free will. Faizzada argues that the Kantian position is neither a kind of compatibilism nor incompatibilism. The theory of freedom includes the specific concept of intellectual causality as the power to act by principles and for practical reasons. The most innovative feature constitutes the self-determination of rational agents regarding the idea of the noumenal world. Kant's philosophical approach to freedom culminates in the concept of so-called transcendental-practical freedom which prepares the ground for morality.